High-performance, heteroepitaxial, nanolaminate device layers on single-crystal-like, artificial substrates and controlled self-assembly of anostructures within device layers for wide-ranging electrical and electronic applications - Goyal, Amit (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems, 2018)
For many energy and electronic applications, single-crystal-like materials offer the best performance. However, in almost all cases, fabrication of single-crystal form of the relevant material is too expensive. In addition, for many applications, very long or wide materials are required a regime not accessible by conventional single-crystal growth.
Keywords: electronic applications; ferroelectrics; multiferroics; superconductors